Influence of polypropylene fibres on the shear strength of RC beams with web reinforcement - Arslan, Guray; Keskin, Riza Secer Orkun (TAYLOR & FRANCIS LTD, 2019)
The use of various types of fibres within concrete matrix for enhancing structural performances of concrete or reinforced concrete (RC) members has been gaining interest in recent years. While a considerable amount of research has been conducted for using steel fibres, the studies on the other types of fibres are limited. For the purpose of extending our knowledge on polypropylene fibres in RC beams, an experimental programme was carried out for investigating the shear behaviour of polypropylene fibre-reinforced concrete (PFRC) beams. This paper presents the results of beams with web reinforcement divided into three groups according to the shear span-to-effective depth ratio and the amount of web reinforcement. Each group consists of a reference RC beam and three beams with fibre contents of 1.0, 2.0 and 3.0%. The simply supported beams were loaded at mid-span. Experimental results show that the addition of polypropylene fibres enhanced the shear behaviour of RC beams with web reinforcement. Furthermore, an expression for the contribution of web reinforcement was derived by considering the effectiveness of web reinforcement and it was introduced to the equation proposed previously for predicting the shear strength of PFRC beams without web reinforcement. The predictions agree with the experimental results.
Keywords: Fibre-reinforced concrete; beam; shear; polypropylene fibre; EFFECTIVE-DEPTH RATIO; STEEL-FIBER; CONCRETE BEAMS; FIBROUS CONCRETE; SYNTHETIC-FIBERS; BEHAVIOR; STIRRUPS; PREDICTION; Engineering